Respon Mahasiswa dan Generasi Z Tentang Pernikahan Beda Agama - Mhd Isa; Mursal Mursal (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The aim of this research is to understand the views of students and Generation Z regarding interfaith marriages, as well as to highlight the problems that arise in connection with this. The research method used is a descriptive quantitative approach, which focuses on the correlation between factors related to interfaith marriages. This method uses data obtained from surveys or experiments, with a population of 300 people, using a quota sample method or random sampling. In general, the results of research related to interfaith marriages show that the majority of respondents have an understanding of the regulations for interfaith marriages and the potential for conflict in the household due to differences in religious views between partners. However, the majority of ulama in Indonesia prohibit interfaith marriages absolutely based on the teachings of the Islamic religion and the laws in force in Indonesia. Therefore, even though interfaith marriages are recognized as a human right, it is important for couples who want to marry partners from different religions to pay attention to applicable legal regulations and procedure.